Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1955
DOI: 10.1002/jcp.1030460209
|View full text |Cite
|
Sign up to set email alerts
|

A correlated biochemical and histochemical study of succinic dehydrogenase activity in the gastric mucosa of the rat and frog

Abstract: This study is coiicerricd with the possibility of a direct correlation between the secretory functions of the gastric mucosa, and the metabolic activity of its cellular constituents. Since succinic dehydrogenase has been found to be concentrated in the gastric parietal cells (Padykula, ' 5 2 ) , it was possible to investigate whether there is any relationship between enzyme activity and the secretion of hydrochloric acid by these cells. Parallel histochemical and quantitative chemical studies were made on gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
2

Year Published

1958
1958
1970
1970

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
3
6
0
2
Order By: Relevance
“…Experim ental studies on animals showed histochcmical features similar to those found in the hum an stomach [7,19,23,26,29]. Recently, while our studies were still in progress, similar observations were reported by Niem i et al [18] on human stomach biopsies.…”
supporting
confidence: 71%
“…Experim ental studies on animals showed histochcmical features similar to those found in the hum an stomach [7,19,23,26,29]. Recently, while our studies were still in progress, similar observations were reported by Niem i et al [18] on human stomach biopsies.…”
supporting
confidence: 71%
“…After such treatment, an increase in the number of parietal cells exhibiting oxidative enzyme activities was observed, as well as an increase in the amount of activity in each parietal cell (Villarreal and Burgos, 1955). Using homogenates of gastric mucosa Vitale, Jankelson, Connors, Hegsted, and Zamcheck (1956) found a rise in succinic dehydrogenase activity after histamine stimulation.…”
Section: Commentsmentioning
confidence: 96%
“…The mucosa was obtained by peroral biopsies and various enzymes were demonstrated by current histochemical techniques. Although somewhat similar studies were carried out with mice and frogs (Villarreal and Burgos, 1955), work on enzyme changes in human gastric mucosa at the time of writing has apparently been confined to homogenate studies (Vitale, Jankelson, Connors, Hegsted, and Zamcheck, 1956).…”
Section: Commentsmentioning
confidence: 99%
“…Tout particulièrement la réaction pour la déshydrogénasc succinique, représentée surtout par des granules noirâtres de dinitroformazane, est apparue plutôt intense surtout au niveau des grandes de la portion descendante et spécialement dans les cellules bordantes; une activité enzymatique moins intense a été observée au niveau des cellules principales, des glandes de la région pylorique en général, de l'épithélium de revêtement et des cellules mucoïdes du collet glandulaire, comme on Ta décrit précédemment aussi bien chez l'homme [2,3,7,10,12] que chez les animaux, bien qu'avec quelques différences [1,4,8,9,11,13,14]. L'activité de la déshydrogénase glutammique s'est montrée sous forme de granules, pour la plupart rouges-bruns, localisée surtout dans les cellules bordantes des tubules glandulaires, en mesure moindre dans les cellules principales: la réac tion, déjà médiocre en soi-même, s'est montrée très faible au niveau de l'épithélium de revêtement et des cellules mucoïdes du collet.…”
Section: Par U Teo D O Ri Et P G En Tilin Iunclassified
“…En effet leur comportement a été assez uniforme, de sorte que tous les enzymes étudiés ont présenté augm entation plus ou moins évidente de leur activité; ceci atteste une plus grande activité métabolique de la muqueuse et surtout de l'épithélium glandulaire engagé dans la pro duction d'acide chlorhydrique [8,14], Ces remarques sont renforcées par l'augm entation des cellules bordantes que nous avons pu observer dans les nombreuses sections soumises aux colorations de contrôle et de la plus intense réaction enzym atique fréquentem ent notée dans chaque cellule. Ceci semble donc confirmer le rôle de l'hypersécrétion chlorhydrique dans l'établissem ent de la lésion ulcéreuse ou tout au moins dans les phénomènes qui souvent l'accompagnent.…”
Section: Deshydrogenasesunclassified